Pengaruh Stres Kerja Terhadap Kinerja Karyawan PT Bank Sulut Go Cabang Utama - Angel Natasya Tampinongkol; Christien Adriani Karambut; Rolyke Tulangow (Universitas Merdeka Madiun, 2024)
The human resources will improve employee performance and support the achievement of organizational goals, however there are several elements that can influence employee performance, one of which is work stress. The purpose of this research is to determine the environment and organization of PT Bank Sulut Go Main Branch, how work stress affects employee performance, and how to implement a supportive work environment. Data collection techniques are observation and questionnaires. This research uses quantitative research methods with simple linear regression data analysis techniques. The data processing tool uses the SPSS application. The sampling technique was carried out by census. The research was conducted at PT Bank Sulut Go Main Branch with a sample size of 35 employees. The source and type of data used is primary data. The results of the analysis show that work stress influences the performance of PT Bank Sulut Go Main Branch employees. This means that if employee work stress increases, employee performance will also increase, and vice versa. The stress caused by this workload can actually increase employee work results.